Olfactory priming on consumer categorization, recall, and choice. Issue 8 (19th February 2020) - De Luca, Ramona; Botelho, Delane
Abstract: Consumer choices are mostly regulated by pleasurable experiences that arise outside of the individuals' awareness in response to sensory attributes. This research examines the unconscious mechanism underlying consumers' behavior in response to odors applying the priming approach. Five experiments show that individuals' responses to odors involve two mechanisms, one affective (affective priming) and one associative (semantic priming) that impact consumers' categorization, recall, and choice. We found that when individuals perceive an odor as pleasant, their memory for odor‐congruent brand logos (Experiment 1), and categorization of odor‐congruent visual objects (Experiment 2) is improved. Unpleasant odors, instead, improve the categorization of odor‐congruent visual objects only when they are made salient (Experiments 3 and 4). A pleasant odor diffused in the environment also drives consumers toward odor‐congruent choices (Experiment 5), providing evidence that the incidental exposure to odors may induce affective and semantic associations with unrelated objects and behaviors. We also demonstrate that olfactory cues might be more effective than other modality (visual) stimuli to drive consumer responses. An implication for marketing is that odors employed in retail settings not only may induce an experience of pleasure but also promote specific consumer responses, such as categorization, recall, and choice.